Outcomes of Inferior Vena Cava Filter Insertion in Patients with Lower Extremity Deep Vein Thrombosis for Prevention of Pulmonary Thromboembolism: A Single Center Retrospective Analysis - Byung Jin Park; Jae Kyu Kim; Nam Yeol Yim; Hyoung Ook Kim; Yang Jun Kang (대한영상의학회지, 2017)
Purpose To evaluate the mid- and long-term outcomes of inferior vena cava (IVC) filter insertion in patients with underlying deep vein thrombosis for prevention of pulmonary thromboembolism, based on a single center experience.